THE REACTION OF CAPITAL MARKETS IN INDONESIA, SINGAPORE, MALAYSIA, AND THAILAND TOWARDS THE ANNOUNCEMENT OF LOCKDOWN POLICY DURING THE BEGINNING OF THE COVID-19 - Lailatul Fauziah; Lintang Venusita (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2021)
This study aims to examine the stock market’s reaction to the announcement of the implementation of the COVID-19 lockdown policy, examining the differences in abnormal return, and the total volume activity in company shares in Indonesia, Singapore, and Malaysia in responding before and after the announcement of the lockdown policy in the countries. This study uses the even study method and is based on secondary data from news portals and websites. The population and sample used in this study are companies listed in the index with the largest capitalization in each country, including LQ45 in Indonesia, STI in Singapore, FBM KCLI in Malaysia, and SET50 in Thailand. The sample collection technique is based on purposive sampling technique. The research variables are the COVID-19 lockdown policy announcement, abnormal return, trading volume activity (TVA) in the form of trading volume in the companies as the sample group. The results show that the announcement of COVID-19 lockdown policy did not significantly influence the reaction of the capital market but was still used as a basis to make investments decision. The announcement of the COVID-19 lockdown, both before and after the announcement, did not have a significant effect on abnormal returns and trading volume activity in Indonesia, Singapore, Malaysia, and Thailand capital markets.